CITIZEN JOURNALIM PADA KANAL GENSINDO DI SINDONEWS.COM - Muhammad Rizki Maulana Maulana (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
This study aims to determine the mechanism for publishing citizen journalism articles on the Gensindo channel on the Sindonews.com website. This research uses a descriptive qualitative method, with the research subject being Sindonews.com and the object of research is the editorial team of Gensindo. Researchers used interview, observation, and documentation techniques. Selection of informants using a purposive sampling technique. In testing the validity of the data using data triangulation techniques. The results show that the articles produced by citizen journalism are informational and structured. The results of this study also concluded that there are 4 stages of the mechanism for publishing citizen journalism articles, namely first, namely acceptance of citizen journalism articles, Second, editing and selecting articles, Third, approval by the editor-in-chief, and finally publishing articles. Publishing articles submitted by citizen journalism must go through the stages of the mechanism carried out by the Gensindo editorial team before being published on the Gensindo channel.